Contract management practice for the procurement of goods in the public sector in Bangladesh: a case study of LGED - Sarkar, Partha Pradip (BRAC University, 2016)
This dissertation report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.